Sistem Penyewaan Mobil Pada PD. Vika Rental Pangkalpinang Berbasis Web Dengan Model Fast - Supardi, S; Revaldo, R; Fitriyanti, F; Pebriyanto, Eka (LPPM STIKOM Tunas Bangsa, 2023)
In the world of service business in the service sector, service to customers is the most important thing to be able to compete with competitors. Things such as services provided by staff, ease of customers in using services, timeliness, as well as recording and making reports are important things in developing a company, including PD. Vika Rental Pangkalpinang. Currently the process of renting a car, returning a car, and making reports to PD.Vika Rental Pangkalpinang is still done manually and the recording process is still written in a book, making it difficult for the rental party to check the data and storing the data is at risk of being damaged or lost. The development of this web-based car rental system uses the FAST (Framework for the Application of System Thinking) model and to develop this system uses UML (Unified Modeling Language) tools. Results of system development in PD. Vika Rental Pangkalpinang can make it easier for customers to rent a car, access the information they need, and also make things easier for PD. Vika Rental Pangkalpinang in carrying out the car rental transaction process.